واقع الاستهلاك الغذائي الوطني - حبيش ،وهيبة (جامعة الوادي University of Eloued, 2024)
This research paper aims to address food consumption in Algeria resulting from resorting to global markets. Despite the importance of the agricultural sector in ensuring food security, Algeria has not been able to improve it due to natural and climatic factors, in addition to the wrong policies that the development process in Algeria has known since independence. Therefore, giving the utmost importance to increasing food production, diversifying its sources and improving its quality through an agricultural policy with a precise and specific strategy and rational and realistic goals is necessary and urgent. However, Algeria is in a great struggle and struggle to improve the situation, as the agricultural sector contributed more than 14.7 percent of the gross domestic product in 2022, as the value of agricultural production reached about 4550 billion dinars, an increase of 38 percent compared to 2021 (source: Algerian News Agency). This explains the efforts made to improve the current situation and move forward towards achieving food security in the coming years, God willing.
The reality of national food consumption
Keywords: Food security; self-sufficiency; food problem; food imports; food dependency